The role of bureaucracy in the politics of Pakistan (1947-1969) - Ahmed Shaikh, Irfan; Islam, Arshad (IIUM Press, 2017)
Bureaucracy is the backbone of any polity, society or administrative unit, and the strength of a country’s administrative and bureaucratic structures is a key index of national development. Pakistan’s civil service (as with its armed forces, railways and many other institutions) is a direct continuation of the Colonial Government of India. The British colonial system had such inherent strengths for practical governance that in post-independence Pakistan the civil service emerged as the most important power broker, and more often than once it was a king-maker. This book discusses and analyses the impact of the role of the bureaucracy on the political evolution of Pakistan, particularly in the context of Jinnah’s vision regarding the role of civil servants in the affairs of the state. It also examines the factors that led the Pakistani government to take a course entirely different from Jinnah’s ideal. This book helps in developing a comprehensive understanding of South Asian politics and Muslim political development in the postcolonial era. Various studies have been conducted on the role of the civil service in the politics of Pakistan, especially relating to the early days of state formation when it served as a powerbroker, but their results are varied and contradictory. Furthermore, the most detailed accounts are the memoirs of bureaucrats themselves, who often seek to blame manifest deficiencies in Pakistan on the inefficiency and incapability of politicians and the intrinsic difficulties of new states, while highlighting their own contributions to the well-being and development of the country. Few studies have endeavoured to examine and evaluate the existing literature on Pakistani bureaucracy that identify the shortcomings in the system and its operation, thus this book addresses this research gap with a more thorough and extensive examination of the relevant themes, particularly with a comparative study with the civil service system of India.